Un epigrama no censado de Martin de Roa (1586) - Grau Jiménez, Jorge (Cuadernos de Filología Clásica. Estudios Latinos, 2004)
The works of the jesuit Martin de Roa (1559-1637) have been object of very accurate catalogs; however, none of them includes a latin epigram found at the begimming of the book titled El Perfecto Regidor (Salamanca 1586). The author of the article explains the reasons why he considers this poem to be a work of Roa, as well as the confusions that had motivated others scholars not to attribute it to his writings before. Following this explanation, the edition of the epigram is presented, followed by its translation into spanish